Mission impossible? Entrepreneurial universities and peripheral regional innovation systems. Issue 2 (17th February 2016) - Brown, Ross
Abstract: As part of their 'third mission' to commercialise research and cultivate growth in local economies, universities have been accorded a central role in regional innovation systems. This paper takes issue with this policy emphasis. It presents empirical evidence suggesting the entrepreneurial spillovers from universities have been greatly exaggerated, especially in some peripheral regions. The explanation offered for this poor performance hinges on the substantive disconnect between universities and their surrounding local entrepreneurial and innovation ecosystems. Despite their marginal economic contribution, the paper claims that 'policy entrepreneurs' play a powerful role in cumulatively reinforcing the dominant role of universities through a process of 'institutional capture', the outcome of which results in a form of 'policy lock-in'. The implications of these findings for public policy are outlined.